2019
DOI: 10.24235/ileal.v5i1.5210
|View full text |Cite
|
Sign up to set email alerts
|

Kesalahan Morfologi Pada Teks Eksplanasi Siswa SMA Negeri 7 Cirebon

Abstract: Tati Sri Uswati, dkk. (Analisis Kesalahan ...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
2
0
4
Order By: Relevance
“…Therefore, it is necessary to analyze language errors in the field of morphology which can be used as a reference for students' language skills so that they can help students find out their mistakes. In line with these research problems, Maulindah and Uswati (2019) found that morphological errors in students' explanatory texts were caused by factors such as lack of references, motivation, and mastery of language rules. The researcher suggests that effective and targeted education be given to improve the quality of students' written language.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Therefore, it is necessary to analyze language errors in the field of morphology which can be used as a reference for students' language skills so that they can help students find out their mistakes. In line with these research problems, Maulindah and Uswati (2019) found that morphological errors in students' explanatory texts were caused by factors such as lack of references, motivation, and mastery of language rules. The researcher suggests that effective and targeted education be given to improve the quality of students' written language.…”
Section: Introductionmentioning
confidence: 78%
“…Affixation errors in the explanation text include omission of affixes, abbreviations of morphs, and inappropriate use of affixes. The removal of affixes is caused by savings that do not need to happen because they are misused (Maulindah & Uswati, 2019). The mistake of removing affixes made by students was the omission of the prefix (meN-).…”
Section: Affix Errormentioning
confidence: 99%
“…Hal ini sangat penting untuk pembelajaran bahasa karena morfologi bersangkutan dalam pembentukan kata dan morfem yang merupakan dasar dari berbagai komponen bahasa seperti frase, klausa, kalimat, paragraf, dan wacana (Mulyanto & Nurjaman, 2023). Proses morfologis mencakup penggabungan kata (komposisi atau pemajemukan), pembubuhan afiks (afiksasi), dan pengulangan kata (reduplikasi) (Maulindah & Uswati, 2019). Semua proses ini melibatkan pembentukan kata dari bentuk dasar.…”
Section: A Pendahuluanunclassified
“…Kesalahan yang ditemukan dalam tulisan teks narasi siswa kelas VII SMP PGRI 13 Gondangrejo di antaranya adalah kesalahan penulisan afiksasi, reduplikasi (pengulangan), dan pemajemukan (komposisi). Jenis kesalahan penulisan afiksasi yang ditemukan, yaitu pelesapan prefiks meN-, pelesapan prefiks ber-, pelesapan fonem /n/ pada sufiks -nya, penyingkatan prefiks meng-, penulisan prefiks meN-, penulisan prefiks di-, penulisan sufiks -kan, penulisan konfiks di-kan. Pada penelitian Maulindah & Uswati (2019)…”
Section: Pemanfaatannya Sebagai Modul Ajar Bahasa Indonesia DI Sekola...unclassified
“…Dengan begitu, bahasa memiliki peran penting bagi manusia untuk menyampaikan dan mengomunikasikan pendapatnya kepada mitra tuturnya. Namun dalam proses berbahasa dan berkomunikasi tidak luput dari kesalahpahaman dan perbedaan pendapat karena adanya perbedaan dalam memahami suatu kaidah bahasa (Pranowo, 2014); (Maulindah & Uswati, 2019); (Agustina & Oktavia, 2019); (A Alber & Febria, 2018); (Wahyu Oktavia, 2018); (Alber Alber & Hermaliza, 2020); (A Alber & Hermaliza, 2021). Perbedaan pemahaman tersebut dapat terjadi pada tiap tataran linguistik, seperti fonologi, semantik, sintaksis, morfologi, maupun wacana.…”
Section: Pendahuluanunclassified